Mortality and cancer incidence in carriers of constitutional t(11;22)(q23;q11) translocations: A prospective study. Issue 6 (11th January 2019) - Schoemaker, Minouk J; Jones, Michael E; Higgins, Craig D; Wright, Alan F; ,; Swerdlow, Anthony J
Abstract : The constitutional t(11;22)(q23;q11) translocation is the only recurrent non‐Robertsonian translocation known in humans. Carriers are phenotypically normal and are usually referred for cytogenetic testing because of multiple miscarriages, infertility, or having aneuploidy in offspring. A breast cancer predisposition has been suggested, but previous studies have been small and had methodological shortcomings. We therefore conducted a long‐term prospective study of cancer and mortality risk in carriers. We followed 65 male and 101 female carriers of t(11;22)(q23;q11) diagnosed in cytogenetic laboratories in Britain during 1976–2005 for cancer and deaths for an average of 21.4 years per subject. Standardised mortality (SMR) and incidence (SIR) ratios were calculated comparing the numbers of observed events with those expected from national age‐, sex‐, country‐ and calendar‐period‐specific population rates. Cancer incidence was borderline significantly raised for cancer overall (SIR = 1.56, 95% CI: 0.98–2.36, n = 22), and significantly raised for invasive breast cancer (SIR = 2.74, 95% CI: 1.18–5.40, n = 8) and in situ breast cancer (SIR = 13.0, 95% CI: 3.55–33.4, n = 4). Breast cancer risks were particularly increased at ages <50 (SIR = 4.37, 95% CI: 1.42–10.2 for invasive, SIR = 22.8, 95% CI: 2.76–82.5 for in situ ). Mortality was borderline significantly raised for breast cancer (SMR = 4.82, 95% CI: 0.99–14.1) but not significantly raised for other cancers or causes. Individuals diagnosed with t(11;22)(q23;q11) appear to be at several‐fold increased breast cancer risk, with the greatest risks at premenopausal ages. Further research is required to understand the genetic mechanism involving 11q23 and 22q11 and there may be a need for enhanced breast cancer surveillance among female carriers. Abstract : What's new? The constitutional translocation between chromosome bands 11q23 and 22q11 is recurrent in human populations, with highly consistent breakpoints. A breast cancer predisposition among carriers has been suggested, but previous studies have been small and had methodological shortcomings. In this first long‐term follow‐up study of site‐specific cancer and mortality risks among carriers, an increased risk of breast cancer was observed compared to the general population, with greatest risks in younger women. The results suggest that carriers of t(11;22)(q23;q11) may require enhanced surveillance for breast cancer and point to the importance of the chromosomal regions 11q23 and 22q11 in breast cancer development.